2007
DOI: 10.1177/0145721707304476
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Transtheoretical Model to Enhance Resources and Supports for Diabetes Self Management

Abstract: Diabetes Initiative grantees have demonstrated that the TTM enhances RSSM and facilitates the adoption of good diabetes self-management behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Individualized assessments allow providers to explore the patient's perspective on glaucoma and how it will impact their life. 12,13 They were significantly more likely to ask African American patients about their views of glaucoma and about their confidence in using glaucoma medications regularly than non-African American patients. This could be because prior work has found that African Americans are less adherent to their glaucoma medications than White patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Individualized assessments allow providers to explore the patient's perspective on glaucoma and how it will impact their life. 12,13 They were significantly more likely to ask African American patients about their views of glaucoma and about their confidence in using glaucoma medications regularly than non-African American patients. This could be because prior work has found that African Americans are less adherent to their glaucoma medications than White patients.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed coding tool was developed over a one-year period using aspects of the key resources and supports for self-management model (RSSM) as a guide. 12,13,19 The transcripts were reviewed by a research assistant who met twice a month with the investigators to develop and refine the coding rules.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research has yet to address how the IDF recommended components of knowledge, problem-solving barriers to change and self-management needs present within a diverse, medically underserved population. A wealth of research has focused on the application of multiple health behavior models to self-management behaviors [9,10]. One such model, the transtheoretical model (TTM), utilizes a staged approach to understand how individual differences in readiness to change health behaviors unfold [11].…”
Section: Introductionmentioning
confidence: 99%